Photoperiod Extension Enhances Lettuce Performance Across LED Spectra in an Indoor Vertical Farming Setup - Fajar Riyadi; Parwati Wiwin Dyah Ully; Yovi Avianto (Jurnal Biologi Tropis, 2026)
Artificial lighting is a key factor in indoor vertical farming because light spectrum and photoperiod strongly regulate plant growth, biomass accumulation, and pigment formation. Lettuce is highly responsive to light manipulation, making it an important model crop for evaluating lighting strategies that can improve productivity and quality under controlled environments. This study evaluated the effects of LED light color and photoperiod on the growth, yield, and pigment content of lettuce (Lactuca sativa L.) cultivated in an indoor vertical farming system in Yogyakarta, Indonesia (November 2025 – January 2026). A 3 × 3 factorial experiment arranged in a nested design was conducted with three light colors (white, blue, and green) and three photoperiods (8, 12, and 16 h). Data were analyzed using ANOVA (α = 0.05), followed by Tukey's HSD when significant differences were detected. Growth and yield were assessed using stem diameter, plant height, number of leaves, leaf area, root length, fresh weight, and dry weight, while physiological responses were evaluated using chlorophyll a, chlorophyll b, and total chlorophyll. Significant light color × photoperiod interactions were observed for stem diameter, root length, fresh and dry weight, and chlorophyll contents. Overall, white light produced superior lettuce performance compared with blue and green light, particularly under a 16-h photoperiod. The combination of white light and a 16-h photoperiod resulted in the highest biomass accumulation and pigment content, indicating that optimizing both light spectrum and photoperiod is critical to improve lettuce productivity and quality in indoor vertical farming.